PROCEEDINGS OF the 29th Quadrennial Session of the CIE 2019
DOI: 10.25039/x46.2019.pp30
|View full text |Cite
|
Sign up to set email alerts
|

Circadian Light Exposures of Shift Working Nurses

Abstract: Studies have linked adverse health outcomes to work during the body's subjective night. Certain shift schedules result in light exposure profiles that may cause circadian disruption. Previous studies estimated average artificial illuminance to quantify light at night (LAN) at work which limits their validity and scope. However, daylight, shift length, commuting exposures and light during restricted sleep opportunities compete with LAN as causative agents, as do non-photic factors such as social disruption, act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…In total, 104 studies were deemed eligible and formed the set of dosimetry field studies reviewed here. An overview of the selected studies 10 …”
Section: Review Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…In total, 104 studies were deemed eligible and formed the set of dosimetry field studies reviewed here. An overview of the selected studies 10 …”
Section: Review Methodsmentioning
confidence: 99%
“…Some studies additionally examined the light data for smooth periods with little fluctuation, indicating invalid periods. 31,69,81 Furthermore, several methods for identifying measurement artefacts due to sensor obstruction have been reported. Some studies ( N = 13) identified artefacts as light measurements below a threshold value during day- or wake-time, ranging from 0 lx to10 lx across studies.…”
Section: Methodological Considerationsmentioning
confidence: 99%
See 3 more Smart Citations